2020
DOI: 10.1111/jocn.15384
|View full text |Cite
|
Sign up to set email alerts
|

Effects of illness representation‐focused patient education on illness representations and self‐care in patients with heart failure: A randomised clinical trial

Abstract: Aims and objectives To examine the effect of an illness representation‐focused patient education intervention on illness representations and self‐care behaviours in patients with heart failure 3 months after discharge from the hospital. Background Few intervention studies have examined the effect of illness representation‐focused interventions on illness representations and self‐care in patients with heart failure. Design A randomised clinical trial based on the Consolidated Standard of Reporting Trials—CONSOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
(50 reference statements)
1
7
0
Order By: Relevance
“…The current review results demonstrated that nurse‐led telecoaching effectively enhances self‐care confidence and maintenance of HF patients. This finding fills the gap in previous evidence, which showed the inconsistent effect of nurse‐led telecoaching on self‐care behaviour (Chang et al, 2020; Chen et al, 2018; Yu, Lee, et al, 2015). In this review, nurses promoted self‐care through telecoaching, consisting of education, physical examinations, psychosocial support and symptoms management (Hwang et al, 2020; Yu, Lee, et al, 2015; Yu, Lee, et al, 2015).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The current review results demonstrated that nurse‐led telecoaching effectively enhances self‐care confidence and maintenance of HF patients. This finding fills the gap in previous evidence, which showed the inconsistent effect of nurse‐led telecoaching on self‐care behaviour (Chang et al, 2020; Chen et al, 2018; Yu, Lee, et al, 2015). In this review, nurses promoted self‐care through telecoaching, consisting of education, physical examinations, psychosocial support and symptoms management (Hwang et al, 2020; Yu, Lee, et al, 2015; Yu, Lee, et al, 2015).…”
Section: Discussionsupporting
confidence: 77%
“…Finally, only a few studies were guided by a theoretical framework, which was considered the unique characteristic of nurse‐led intervention. Several nurse‐led interventions were delivered based on the theoretical framework because of the ability to ensure knowledge transfer effectiveness (Chang et al, 2020; Chen et al, 2018; Dekker et al, 2012; Hsu et al, 2020; Sadeghi Akbari et al, 2019). In future studies, it is warranted to consider these aspects when developing nurse‐led telecoaching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self‐management can reduce treatment‐related side effects and the likelihood of secondary complications (Chou, 2019), so it is important for cervical cancer survivors. Behaviours of self‐management may be influenced by information from past experience and sensations (Chang et al, 2020); therefore, how patients perceive cervical cancer can affect adherence to self‐management.…”
Section: Introductionmentioning
confidence: 99%
“…Heart failure is associated with various physical and psychological stressors such as pain, lack of health, job loss, sensory deprivation, the feeling of imminent death and leads to varying degrees of psychological reactions such as frustration, fatigue and panic, worthlessness, and anxiety. Depression occurs in the patient [7,8].…”
Section: Introductionmentioning
confidence: 99%